Hearing Screening to Evaluate the Status of Newborn Hearing Impairment in the NICU of a Tertiary Hospital - Shameem, Md; Saha, Kanu Lal; Uddin, Md Belal; Jahan, Jesmin; Bhuiyan, ANM Nurul Haque; Masoom, Ahsan Kabir (TAJ: Journal of Teachers Association, 2022)
Introduction: One to three per 1,000 live births suffers from significant hearing impairment. However, 2 to 4 per 100 infants who survived neonatal intensive care have some degree of sensorineural hearing loss. If hearing impairment in newborns is detected earlier, early management can prevent undesirable and often irreversible damage due to late detection. Early detection and the treatment of hearing impairment in children are essential for the development of communication skills, social skills, emotional well-being, and positive self-esteem. Unfortunately, this disability remains undetected for many newborns until it is too late to prevent undesirable and often irreversible damage. Unfortunately, not many studies were done on this topic in Bangladesh. The magnitude of the burden of hearing impairment in the study place might be identified by this study. The objective of the study: Hearing screening was done to see the status of hearing impairment in newborns admitted to NICU. Methodology: A prospective observational study was conducted in the department of neonatology, BSMMU. Newborn admitted to the NICU during the study period was the study population. The newborn who met the inclusion criteria was screened with TEOAE close to discharge from the NICU or before one month of age. A second screen was done with TEOAE again after one month of 1st screen but prior to 3 months of postnatal age if referred in 1st screen. Diagnostic ABR was done prior to 3 months of the postnatal age if referred in both the 1st and 2nd screen. Results: 426 valid recordings from 493 newborns admitted to the NICU enrolled consecutively constitute the basis of this study. Fourteen newborns were found to have hearing impairment among 426 newborns (3.3%). 2 newborns had unilateral hearing loss, and their hearing losses were moderate in nature. The other 12 newborns in their 24 ears had different grades of hearing loss. It was mild hearing loss in 3 ears, moderate in 9 ears, severe in 8 ears, and profound in 4 ears. Conclusion: Hearing screening showed that 3.3% of newborns in the NICU have a hearing impairment. It is still an underestimation considering the number of newborns who were lost to follow-up. TAJ 2022; 35: No-1: 77-82